An experimental investigation on CTCs transfer methods using glass capiliary tube and magnetic rod - Zhe Ning, Oh (2016)
There has been an increase in interest in reducing the current timeframe for detection of cancer cells (CTCs analysis). Timing is a crucial component as fast CTCs detection reduces the spread of CTCs to other organs of the patient’s body. Several disadvantages existed in the current methods used in CTCs extraction for cancer analysis, including the cost, long duration incurred to get the results and most essentially, the disappointing low yield of CTCs being captured. Presently, only one method of CTCs extraction is approved by the US Food and Drug Administration (FDA), the CellSearch™ method [31]. However, CellSearch™ is only applicable to a limited range of cancer detection [23], which are colon, metastatic breast and prostate cancer. There is a market for CTCs detection methods that are simple and provide quick results, for other types of CTCs detection which the CellSearch™ method can’t perform, like lung cancer cells. Currently, the public can only rely on pooled data from clinical applications of the various CTCs detection methods, which are not approved by FDA, to perform CTCs analysis. The difficulty for the FDA certification for other CTCs method is due to the difficulties for routine use as there lacks a framework to ensure reproducibility of the results. Two different CTCs transfer methods are proposed by the author, in order to shorten the current CTCs extraction time. The author’s intention is to conduct the experiments and obtain the results to find out their feasibility and the best encapsulation materials in CTCs transfer. The author conducted experiments on these two particular methods of CTCs extraction, otherwise known as CTCs transfer. In the first method, the author used a glass capillary tube to suck in the CA10 beads (10 μm polymer beads) from CA10 solution and release the CA10 beads into distilled water, using pressure differences in the capillary tube and the surrounding solution. Next, the author used two magnetic rods (soft iron rod and steel wire) with various encapsulation materials, to attract the Dynabeads® (2.8 μm magnetic nanoparticles), and then release them in distilled water.